Letter to Jane Tolmach from Edison P. McDaniels - Edison P. McDaniels:::::: (1970)
In this November 17, 1970 letter, Assembly nominee Edison P. McDaniels thanks Jane Tolmach for reminding him to nominate women volunteers for the Key Women Award Party. He explains that he does not have all the nominees' addresses and suggests forwarding invitations through the local Democratic County Committee chairman if necessary. McDaniels encloses a separate list of his nominees and expresses appreciation for the recognition of his campaign supporters.